Siderophore‐Linked Ruthenium Catalysts for Targeted Allyl Ester Prodrug Activation within Bacterial Cells. Issue 8 (21st December 2022) - Southwell, James W.; Herman, Reyme; Raines, Daniel J.; Clarke, Justin E.; Böswald, Isabelle; Dreher, Thorsten; Gutenthaler, Sophie M.; Schubert, Nicole; Seefeldt, Jana; Metzler‐Nolte, Nils; Thomas, Gavin H.; Wilson, Keith S.; et al.
Abstract: Due to rising resistance, new antibacterial strategies are needed, including methods for targeted antibiotic release. As targeting vectors, chelating molecules called siderophores that are released by bacteria to acquire iron have been investigated for conjugation to antibacterials, leading to the clinically approved drug cefiderocol. The use of small‐molecule catalysts for prodrug activation within cells has shown promise in recent years, and here we investigate siderophore‐linked ruthenium catalysts for the activation of antibacterial prodrugs within cells. Moxifloxacin‐based prodrugs were synthesised, and their catalyst‐mediated activation was demonstrated under anaerobic, biologically relevant conditions. In the absence of catalyst, decreased antibacterial activities were observed compared to moxifloxacin versus Escherichia coli K12 (BW25113). A series of siderophore‐linked ruthenium catalysts were investigated for prodrug activation, all of which displayed a combinative antibacterial effect with the prodrug, whereas a representative example displayed little toxicity against mammalian cell lines. By employing complementary bacterial growth assays, conjugates containing siderophore units based on catechol and azotochelin were found to be most promising for intracellular prodrug activation. Abstract : Ganging up on bacteria : Siderophore‐linked ruthenium catalysts were investigated for the activation of an antibacterial prodrug within cells. A fluoroquinolone prodrug was developed and shown to be compatible with the catalysts under micro‐aerobic, biologically relevant conditions. The co‐addition of the catalysts and prodrug to E. coli showed a combinative effect, with the dihydroxybenzoic acid‐ and azotochelin‐linked catalysts showing most promise for cellular uptake and thus intracellular prodrug activation.